"How Many Individuals Consider Themselves to Be Cell Biologists but Are Informed by the Journal That Their Work Is Not Cell Biology". Issue 3 (9th September 2022) - Worliczek, Hanna Lucia
Abstract: What can we gain from co‐analyzing experimental cultures, regionalization, and disciplinary phenomena of late twentieth century life sciences under our historiographic looking glass? This essay investigates the potential of such a strategy for the case of cell biology after 1960. By merging perspectives from historical epistemology inspired by the work of Hans‐Jörg Rheinberger with a focus on boundary work in the realm of scientific publishing, community building, and disciplinary norms, a set of understudied scientific practices is exposed. These practices, historically subsumed under the label descriptive, have been as central in cell biology as hypothesis‐driven research aiming at mechanistic explanations of cellular function. Against the background of an increasing molecular‐mechanistic imperative in cell biology since the late 1960s, knowledge from descriptive practices was often judged as having low value but was nonetheless frequently cited and considered essential. Investigating the underlying epistemic practices and their interactions with disciplinary gatekeeping phenomena (as policed by journals and learned societies) provides historiographic access to the plurality of experimental cultures of cell biology, scattered into many interdisciplinary research fields—with some of them only partially engaged with mechanistic questions.